Estratégias discursivas e legitimidade: o caso da Klabin S/A e o distrito industrial de Telêmaco Borba/PR - Fragoso, Renata (2012)
The aim of this dissertation is to analyse, regarding both political-economic and environment institutional contexts, how Klabin used coordinative and communicative discursive strategies toward legitimacy of strategic actions undertaking during the development of Telemaco Borba’s industrial district, Parana estate, between 1993-2011. The research was conducted from the standpoint of organizational institutionalism through the articulation of agency with discursive elements located in an embedded agent which discuss the actions in the work of creating the institutional environment. The study design was descriptive. For this purpose, we used a qualitative approach to case study with cross sectional and longitudinal perspectives, since data were collected in national, sectorial and local contexts corresponding to the last two decades. The cut is regarded as a historical landmark in the year 1993, when Klabin started its participation on the development of Telêmaco Borba’s industrial district, until the year 2011, upon completion of data collection. The data identified Klabin’s strategic actions, which five of them stood out because of the relevance in understanding the district’s development. The analysis took into account the actions of boundary work and practice work, the permeability of macro-discourse and oriented legitimacy. Data analysis has shown different discourses associated with the coordination and justification of Klabin’s strategic actions. These discourses, according to the analysis, even delivered in the local context are influenced by political-economic and environmental macro-discourses in both national and sector levels in which Klabin is inserted. Also, it is noted that sociopolitical and cultural-cognitive based justifications are associated with the enterprise’s strategic actions. These results refer to the considerations about the role of the discourse in the construction of organizational legitimacy.